Opioids for management of episodic breathlessness or dyspnea in patients with advanced disease. - Cabezón-Gutiérrez, Luis; Khosravi-Shahi, Parham; Custodio-Cabello, Sara; Muñiz-González, Francisco; Cano-Aguirre, Maria; Alonso-Viteri, Soledad; Cabezón-Gutiérrez, Luis; Muñiz-González, Francisco; Cano-Aguirre, Maria Del Puerto (Supportive Care in Cancer, 2016)
Background: Episodic breathlessness (EB) or dyspnea is a common symptom with a very negative impact on the quality of life of patients with cancer and with non-oncological advanced diseases, mainly cardiorespiratory and neurological.Objective: The purpose of this non-systematic review is to ascertain the role played by opioids in the management of episodic breathlessness.Methods: A non-systematic literature review was done in the databases MEDLINE, COCHRANE, and DATABASE, and articles of greater scientific rigor, mainly reviews or prospective studies/randomized clinical trials published to date (August 2015), were selected. Terms used in the search included episodic breathlessness, acute breathlessness, episodic dyspnea, opioids, morphine, fentanyl, oxycodone, and breakthrough dyspnea.Conclusions: Although the pathophysiology and mechanism of action of opioids for management of breathlessness, and specifically EB, are not fully known, there is scientific evidence, and particularly great clinical evidence, of the benefit of this drug class for dyspnea management. It is important to differentiate hospitalized patients from outpatients because venous or subcutaneous access is easier in hospitalized patients, but use of transmucosal fentanyl, especially in faster formulations like intranasal application, opens up new possibilities to manage outpatients due to its fast onset of action. The main problem is the lack of data available and the multitude of unanswered questions about opioid type, administration route, safety, and dose titration.